2021
DOI: 10.2174/2352096514666210617125102
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Three-dimensional Node Localization Algorithm Using Dynamic Path Planning

Abstract: Background: In the applications of wireless sensor network technology, three-dimensional node location technology is crucial. The process of node localization has some disadvantages, such as the uneven distribution of anchor nodes and the high cost of the network. Therefore, the mobile anchor nodes are introduced to effectively solve accurate positioning. Objective: Considering the estimated distance error, the received signal strength indication technology is used to optimize the measurement of the distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…ANP technology provides location information for athletes, and this method can evaluate the quality of movement of athletes. This study combines this method with motion sensor technology, as shown in Formula (6) [16]. This method can not only classify the user's movement behavior, but also analyze the user's posture change information.…”
Section: Physical Fitness Datamentioning
confidence: 99%
“…ANP technology provides location information for athletes, and this method can evaluate the quality of movement of athletes. This study combines this method with motion sensor technology, as shown in Formula (6) [16]. This method can not only classify the user's movement behavior, but also analyze the user's posture change information.…”
Section: Physical Fitness Datamentioning
confidence: 99%
“…The 6th cluster is related to location awareness in IoT, and position estimation using UAV anchors [34]. The 7th and 8th clusters are related to the WSN dynamic environment and accuracy [18,19,32,37].…”
Section: Keyword Co-occurrence and Co-author Analysismentioning
confidence: 99%
“…Researchers who are close together tend to cite the same publication or collaborate, whereas researchers with nodes that are far apart usually do not cite or collaborate on the same publication. For example, Liu Y collaborated with Yang C in research on the dynamic path planning method on mobile anchors [37]. Liu Y also collaborated with Shen Y in his research on single anchor passive localization [38].…”
Section: Keyword Co-occurrence and Co-author Analysismentioning
confidence: 99%